Photoelectric conversion element
Patent Information
- Application Number
- JP2024032815
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-01
- Filing Date
- 2024-03-05
- Publication Date
- 2025-02-14
AI Technical Summary
【0007】 実施形態の光電変換素子は、基板と、前記基板上に配置された第1電極と、前記第1の電極上に配置され、 組成式:ABX3 (式中、Aはアミン化合物の1価陽イオンであり、Bは金属元素の2価陽イオンであり、Xはハロゲン元素の1価陰イオンである。) で表される組成を有するペロブスカイト結晶を含む光電変換膜と、前記光電変換膜上に配置された電子輸送層と、前記電子輸送層上に配置された第2電極とを具備する。実施形態の光電変換素子において、前記第2電極は、前記電子輸送層上に配置され、チタン、スズ、亜鉛、セリウム、インジウム、及びニオブからなる群より選ばれる少なくとも1つの第1金属、及び前記第1金属の酸化物を含む第1層と、前記第1層上に配置され、第2金属及び前記第2金属の酸化物を含む第2層とを備え、前記第2層は、前記第1層側に存在する第1領域と、前記第1領域上に存在し、前記第1領域より低い酸素濃度を有する第2領域と、前記第2領域上に存在し、前記第2領域より高い酸素濃度を有する第3領域とを備える。
Smart Images

Figure 2025022707000001_ABST
Abstract
Description
[Technical field]
[0001] An embodiment of the present invention relates to a photoelectric conversion element. [Background technology]
[0002] Photoelectric conversion elements such as solar cells, photosensors, light-emitting elements, photodiodes, and optical memories that use perovskite-type materials as photoelectric conversion materials are expected to be low-cost photoelectric conversion elements because inexpensive coating methods can be applied to layer formation. Among the perovskite-type materials used as photoelectric conversion materials, perovskite crystals with a composition represented by ABX3 and a three-dimensional crystal structure have excellent photoelectric conversion efficiency, and solar cells and the like that use them to improve conversion efficiency have been reported. One of the challenges of such solar cells is the corrosion resistance and conductivity of the electrode (cathode) formed on the photoelectric conversion layer.
[0003] A photoelectric conversion element using a perovskite material has a structure in which an anode, a photoelectric conversion layer, an electron transport layer, and a cathode are laminated on a transparent substrate. In such a photoelectric conversion element, a laminate structure of a layer containing chromium (Cr) and Cr oxide and a layer of gold (Au), copper (Cu), aluminum (Al), etc. formed thereon has been proposed for the cathode. However, since Cr oxide is a p-type semiconductor, if it is placed on the electron transport layer side, it becomes a barrier to electron transport, which leads to a decrease in efficiency. Furthermore, since only one layer containing an oxide is placed in the cathode, it is not possible to sufficiently increase the blocking ability from the external environment. For this reason, the Au layer on the upper layer side is easily deteriorated due to corrosion from the external environment. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 6989391 [Non-patent literature]
[0005] [Non-Patent Document 1] Nature materials 14.10 (2015):1032-1039 Summary of the Invention [Problem to be solved by the invention]
[0006] The problem to be solved by the present invention is to provide a photoelectric conversion element which has a sufficiently enhanced blocking ability from the external environment, suppresses deterioration of characteristics, and has improved electronic efficiency and electrical conductivity. [Means for solving the problem]
[0007] The photoelectric conversion element of the embodiment includes a substrate, a first electrode disposed on the substrate, and a second electrode disposed on the first electrode. Composition formula: ABX3 (In the formula, A is a monovalent cation of an amine compound, B is a divalent cation of a metal element, and X is a monovalent anion of a halogen element.) The photoelectric conversion element of the embodiment includes a photoelectric conversion film including a perovskite crystal having a composition represented by the formula: an electron transport layer disposed on the photoelectric conversion film; and a second electrode disposed on the electron transport layer. In the photoelectric conversion element of the embodiment, the second electrode includes a first layer disposed on the electron transport layer and including at least one first metal selected from the group consisting of titanium, tin, zinc, cerium, indium, and niobium, and an oxide of the first metal, and a second layer disposed on the first layer and including a second metal and an oxide of the second metal, and the second layer includes a first region present on the first layer side, a second region present on the first region and having a lower oxygen concentration than the first region, and a third region present on the second region and having a higher oxygen concentration than the second region. [Brief description of the drawings]
[0008] [Figure 1] 1 is a cross-sectional view showing a first example of a photoelectric conversion element according to an embodiment. [Diagram 2] FIG. 4 is a cross-sectional view showing a second example of a photoelectric conversion element according to an embodiment. [Diagram 3]FIG. 4 is an IV curve diagram of the photoelectric conversion element of Example 1. [Figure 4] FIG. 4 is an IV curve diagram of the photoelectric conversion element of Comparative Example 1. [Diagram 5] 1 is an enlarged photograph showing a state of an Al electrode 100 hours after production of the photoelectric conversion element of Example 1. [Figure 6] 1 is an enlarged photograph showing a state of an Al electrode 100 hours after production of the photoelectric conversion element of Comparative Example 1. [Figure 7] 4 is a diagram showing the results of XPS analysis of the Al component at locations corresponding to the third region, the second region, and the first region in the Al electrode of the photoelectric conversion element in Example 1. FIG. [Figure 8] 4 is a diagram showing the results of XPS analysis of the Ti component in the vicinity of a first region of the photoelectric conversion element in Example 1. FIG. [Figure 9] 4 is a graph showing the element abundance ratios of an Al electrode and a Ti electrode in the photoelectric conversion element of Example 1. [Figure 10] 13 is a diagram showing the results of XPS analysis of the Al component at locations corresponding to the third region, the second region, and the first region in the Al electrode of the photoelectric conversion element of Comparative Example 1. FIG. [Figure 11] 1 is a graph showing the element abundance ratios of an Al electrode and a Ti electrode in a photoelectric conversion element of Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, the photoelectric conversion element and the manufacturing method thereof according to the embodiment will be described with reference to the drawings. In each embodiment, the same reference numerals are used for substantially the same components, and the description thereof may be omitted. The drawings are schematic, and the relationship between thickness and planar dimensions, the ratio of thickness of each part, etc. may differ from the actual ones. Terms indicating directions such as up and down in the description indicate relative directions in the case where the formation surface of each layer of the substrate described later is the top, unless otherwise specified, and may differ from the actual directions based on the direction of gravitational acceleration.
[0010] Fig. 1 is a cross-sectional view showing a first example of a photoelectric conversion element according to an embodiment. The photoelectric conversion element 100 shown in Fig. 1 includes a transparent substrate 110 as a support substrate, a first electrode 120 arranged on the transparent substrate 110, a photoelectric conversion film 130 arranged on the first electrode 120, an electron transport layer 140 arranged on the photoelectric conversion film 130, and a second electrode 150 arranged on the electron transport layer 140. Each of the constituent layers will be described in detail below.
[0011] Here, since the photoelectric conversion element 100 is assumed to be the second electrode 150 to which light is irradiated from below in the drawing, a transparent substrate 110 is used as the support substrate. A material having light transmissive and insulating properties is used for the transparent substrate 110. The constituent material of the transparent substrate 110 is inorganic material such as alkali-free glass, quartz glass, sapphire, etc., or organic material such as polyethylene (PE), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polyimide, polyamide, polyamideimide, liquid crystal polymer, etc. The transparent substrate 110 may be a rigid substrate made of an inorganic material or an organic material, or may be a flexible substrate made of an organic material or an extremely thin inorganic material.
[0012] The first electrode 120 disposed on the transparent substrate 110 is a transparent electrode serving as an anode, and is made of a material having optical transparency and electrical conductivity. Examples of materials constituting the first electrode 120 include conductive metal oxides such as indium oxide, zinc oxide, tin oxide, indium tin oxide (ITO), fluorine-doped tin oxide (FTO), indium zinc oxide (IZO), and indium gallium zinc oxide (IGZO), conductive two-dimensional layered compounds such as titanium carbide and titanium aluminum carbide, thin films of metals such as gold, platinum, silver, copper, titanium, zirconium, cobalt, nickel, indium, and aluminum, and alloys containing these metals, conductive polymer materials such as poly(3,4-ethylenedioxythiophene) / poly(4-styrenesulfonic acid) (PEDOT / PSS), and carbon compounds such as graphene and carbon nanotubes. The first electrode 120 is formed by, for example, a vacuum deposition method, a sputtering method, an ion plating method, a plating method, a coating method, or the like.
[0013] The photoelectric conversion film 130 is a perovskite crystal layer. The perovskite crystal has a composition represented by the following formula (1) and has a three-dimensional crystal structure. Composition formula: ABX3…(1) In formula (1), A is a monovalent cation of an amine compound, B is a divalent cation of a metal element, and X is a monovalent anion of a halogen element.
[0014] Perovskite crystal structures are divided into four types, from zero-dimensional structures to three-dimensional structures. Two-dimensional structures having a composition represented by A2BX4 and three-dimensional structures having a composition represented by ABX3 are advantageous in obtaining highly efficient photoelectric conversion materials and photoelectric conversion elements using the same. Of these, three-dimensional structures are known to have low exciton binding energy, and are more preferable in obtaining highly efficient photoelectric conversion materials and photoelectric conversion elements. It is known that when the ionic radius of the A site is large, a two-dimensional structure is obtained, and when it is small, a three-dimensional structure is obtained.
[0015] It is empirically known that when the A-site ion has an ionic radius with a tolerance factor t between 0.75 and 1.1, it forms a three-dimensional perovskite crystal. The tolerance factor t is a value expressed by the following formula (2). There are several types of ionic radii, but the Shannon ionic radius is used. t = (A site ion radius + X site ion radius) / {2 1 / 2 ×(B site ion radius + X site ion radius)}…(2)
[0016] In order to satisfy the conditions for the A site ions as described above, the A site is composed of a monovalent cation of an amine compound. The amine compound that composes the A site is preferably at least one selected from methylammonium (CH3NH2) and formamidinium (NH2CHNH). The B site is composed of a divalent cation of a metal element, and the X site is composed of a monovalent anion of a halogen element. The metal element that composes the B site is preferably at least one selected from lead (Pb) and tin (Sn). The halogen element that composes the X site is preferably at least one selected from iodine (I), bromine (Br), and chlorine (Cl). These provide high photoelectric conversion efficiency.
[0017] The thickness of the photoelectric conversion film 130 is preferably in the range of 10 to 1000 nm. The photoelectric conversion film 130 can be formed by applying a dispersion of a coating liquid (perovskite crystal) in which a photoelectric conversion material such as perovskite crystal is dispersed in a dispersion liquid onto the transparent substrate 110, and then scattering and drying the dispersion liquid to form a perovskite crystal layer. As a coating mechanism for the photoelectric conversion material dispersion liquid, any method (and mechanism) that can supply the photoelectric conversion material dispersion liquid with a uniform film thickness onto the film formation target can be used, and liquid coating methods such as spin coating, slit coating, screen printing, spraying, and meniscus coating can be used.
[0018] The photoelectric conversion film 130 is irradiated with light such as sunlight or illumination light from, for example, the transparent substrate 110 side. When the photoelectric conversion film 130 made of a perovskite crystal layer absorbs the light irradiated to the photoelectric conversion element 100, electrons and holes that pair with the electrons are generated. Of the electrons and holes generated in the photoelectric conversion film 130, for example, the electrons are collected by the second electrode (cathode) 150 via the electron transport layer 140, and the holes are collected by the first electrode (anode) 120. A hole transport layer may be disposed between the first electrode 120 and the photoelectric conversion film 130.
[0019] The electron transport layer 140 has a function of blocking holes generated in the photoelectric conversion film 130 and selectively and efficiently transporting electrons to the second electrode 150. The electron transport layer 140 may include a metal oxide such as zinc oxide, titanium oxide, or gallium oxide, or a fullerene C 60 , C 70 and fullerene metal complexes, [6,6]phenyl C 61 Butyric acid methyl ester (PC60BM), [6,6]phenyl C 71 Butyric acid methyl ester (PC70BM), Bisindene C 60 Fullerene derivatives such as (60ICBA), organic materials such as polyethyleneimine, perylenediimide derivatives, and naphthalenediimide derivatives are used. When a hole transport layer is applied, the hole transport layer has a function of blocking electrons generated in the photoelectric conversion film 130 and transporting holes selectively and efficiently to the first electrode 120. For the hole transport layer, organic conductive polymers such as PEDOT / PSS, polythiophene, polytolylamine, polypyrrole, triphenylenediamine polypyrrole, and polyaniline, metal oxides such as nickel oxide, copper oxide, tungsten oxide, molybdenum oxide, and vanadium oxide, carbazole-based compounds and polycyclic aromatic compounds having phosphoric acid moieties, carboxylic acids, and silyl ester moieties capable of forming chemical bonds with the first electrode 120, and the like are used. The electron transport layer is formed by a vacuum film formation method such as a vacuum deposition method or a sputtering method, a sol-gel method, a coating method, and the like. The same is true for the hole transport layer.
[0020] The second electrode 150 is made of a material that is conductive and, in some cases, optically transparent. The second electrode 150 is disposed on the electron transport layer 140 and includes a first layer 160 containing at least one first metal selected from the group consisting of titanium (Ti), tin (Sn), zinc (Zn), cerium (Ce), indium (In), and niobium (Nb) and an oxide of the first metal, and a second layer 170 disposed on the first layer 160 and containing a second metal and an oxide of the second metal. The second metal is preferably at least one metal selected from the group consisting of aluminum (Al), molybdenum (Mo), nickel (Ni), copper (Cu), and silver (Ag) that has a higher electrical conductivity than the first metal. Each layer of the second electrode 150 is formed by a vacuum film formation method such as a vacuum deposition method or a sputtering method.
[0021] The second layer 170 in the second electrode 150 includes a first region 171 present on the first layer 160 side, a second region 172 present on the first region 171, and a third region 173 present on the second region 172. The first region 171 has a higher oxygen concentration than the second region 172. In other words, the second region 172 has a lower oxygen concentration than the first region 171. Furthermore, the third region 173 has a higher oxygen concentration than the second region 172. The first region 171 and the third region 173 are preferably in a state in which the second metal and oxygen are bonded together, rather than simply containing oxygen or simply having oxygen adsorbed on the surface. The first region 171 and the third region 173 in such a state have excellent corrosion resistance.
[0022] In the first layer 160 of the second electrode 150, at least one first metal selected from the group consisting of Ti, Sn, Zn, Ce, In, and Nb exhibits properties as an n-type semiconductor when made of an oxide, and therefore does not prevent electrons generated in the photoelectric conversion film 130 from being collected by the second electrode (cathode) 150 via the electron transport layer 140, but rather promotes the movement of electrons. This improves the efficiency of the photoelectric conversion element 100. Furthermore, the oxide of the first metal has excellent corrosion resistance, and therefore contributes to improving the corrosion resistance of the second electrode 150.
[0023] For example, a second layer 170 containing a second metal and an oxide of the second metal having a higher electrical conductivity than the first metal is formed on the first layer 160 containing such a first metal and an oxide of the first metal, and the second electrode 150 is made into a laminated electrode of the first layer 160 containing the oxide of the first metal and the second layer 170 containing the oxide of the second metal, thereby improving the blocking ability against the external environment. Therefore, it becomes possible to improve the electronic efficiency of the photoelectric conversion element 100, sufficiently increase the blocking ability of the second electrode 150 against the external environment, and suppress the deterioration of characteristics due to contamination of the second electrode 150 from the external environment, etc.
[0024] Furthermore, the second layer 170 in the second electrode 150 includes a first region 171 present on the first layer 160 side, a third region 173 present on the outermost layer side, and a second region 172 present between them, and the first region 171 and the third region 173 each have a higher oxygen concentration than the second region 172. By applying such first region 171 and third region 173, the blocking ability of the second layer 170 against the external environment can be improved. Furthermore, since the oxygen concentration of the second region 172 present between them is lower than that of the first region 171 and the third region 173, the conductivity of the second layer 170 due to the second region 172 can be increased. In other words, it is possible to provide a photoelectric conversion element 100 including a second electrode 150 that has improved conductivity originally required for an electrode and blocking ability against the external environment, thereby improving corrosion resistance.
[0025] In the second electrode 150, the first layer 160 preferably has a thickness of 1 nm or more and 50 nm or less, and the second layer 170 preferably has a thickness of 20 nm or more and 400 nm or less. In the second layer 170, the first region 171 preferably has a thickness of 1 nm or more and 30 nm or less, the second region 172 preferably has a thickness of 10 nm or more and 398 nm or less, and the third region 173 preferably has a thickness of 1 nm or more and 30 nm or less. The thicknesses of the first region 171, the second region 172, and the third region 173 in the second layer 170 can be determined by energy dispersive X-ray spectroscopy (TEM-EDX) by transmission electron microscope analysis in the cross-sectional direction, or X-ray photoelectron spectroscopy (XPS) in the depth direction combined with ion sputtering, or the like.
[0026] The first layer 160 and the second layer 170 of the second electrode 150 can be formed by a vacuum film formation method such as a vacuum deposition method or a sputtering method. For example, when the second electrode 150 is formed by applying the vacuum deposition method, the oxygen concentration of each of the first region 171, the second region 172, and the third region 173 can be controlled by changing the pressure or oxygen concentration in a film formation chamber.
[0027] The second electrode 150 may further include a third layer 180, which is disposed on the second layer 170 and contains a third metal, as shown in FIG. 2. As the third metal constituting the third layer 180, for example, a metal that is less likely to oxidize than the second metal can be used. Such metals include at least one selected from the group consisting of copper (Cu), silver (Ag), and gold (Au). By applying the third layer 180 containing such a third metal, the conductivity of the second electrode 15 can be further increased. Alternatively, the third metal may be a metal that is more likely to form a passive state than the second metal. Such metals include at least one selected from the group consisting of titanium (Ti), aluminum (Al), and molybdenum (Mo). By applying the third layer 180 containing such a third metal, the corrosion resistance of the second electrode 15 can be further improved by the passivated third layer 180.
[0028] The photoelectric conversion element 100 of the embodiment includes a second electrode 150 that has improved corrosion resistance by improving blocking ability against the external environment, and has improved electronic efficiency and electrical conductivity. Therefore, it is possible to provide a photoelectric conversion element 100 with improved electrical conductivity, electronic efficiency, and corrosion resistance. The photoelectric conversion element 100 of the embodiment can be applied to solar cells, optical sensors, light-emitting elements, photodiodes, optical memories, and the like. EXAMPLES
[0029] Next, examples and their evaluation results will be described.
[0030] Example 1 [Fabrication of photoelectric conversion element] After forming an ITO film as a first electrode on a PET substrate, ultrasonic cleaning and UV cleaning were performed in isopropyl alcohol and acetone. A hole transport layer containing PEDOT:PSS with a thickness of about 50 nm was formed on the PET substrate having an ITO film. PEDOT:PSS (AI4083 (trade name) manufactured by Heraeus Co., Ltd.) was used as the solution for the hole transport layer. A meniscus coating device with a cylindrical applicator was used for film formation. The applicator was positioned so that the gap distance between the applicator and the PET substrate was 0.2 mm, and 7.5 μL of the hole transport layer solution was supplied to each coating area of the applicator to form a meniscus column. The coating solution was applied onto the PET substrate while controlling the angle and gap distance of the PET substrate. The moving speed of the PET substrate was constant at 8.0 mm / s. This hole transport layer solution was applied onto the PET substrate having an ITO film, and then heated in the atmosphere at 140 °C for 10 minutes to remove excess solvent and form a hole transport layer. The thickness of the hole transport layer was about 50 nm.
[0031] Next, a perovskite layer was formed as a photoelectric conversion layer as follows. First, a perovskite material solution (coating solution) was prepared by dissolving methylammonium iodide (CH3NH3I) and lead iodide (PbI2) in N,N-dimethylformamide (DMF). The molar ratio of methylammonium iodide to lead iodide in the coating solution was 1:1, and the concentration in the solution was adjusted to 45 mass%. A meniscus coating device with a cylindrical applicator was used for film formation. The applicator was positioned so that the gap distance between the applicator and the PET substrate was 0.2 mm, and 7.5 μL of perovskite material solution was supplied to each coating area of the applicator to form a meniscus column. The coating solution was applied onto the PET substrate while controlling the angle and gap distance of the PET substrate. The moving speed of the PET substrate was constant at 100 mm / s, and at the same time as coating, nitrogen gas was blown onto the coating film with an air knife at a wind speed of 6.0 m / s to dry the coating film. After that, it was heated at 120°C for 10 minutes to remove excess solvent and grow crystals, forming a photoelectric conversion layer of perovskite crystal compound. The thickness of the photoelectric conversion layer was approximately 500 nm.
[0032] Next, the solution for the electron transport layer was prepared by adding 1 mL of monochlorobenzene to 20 mg of 60PCBM. The coating head was positioned so that the gap distance between the coating head and the photoelectric conversion layer on the PET substrate was 0.5 mm. 40.0 μL of the solution for the electron transport layer was supplied to each coating area of the coating head to form a meniscus column. The coating solution was applied onto the PET substrate while controlling the angle and gap distance of the PET substrate. The moving speed of the PET substrate was constant at 8.0 mm / s. After applying this solution for the electron transport layer onto the ITO substrate, it was heated in the atmosphere at 100°C for 10 minutes to remove excess solvent and form an electron transport layer. The film thickness of the electron transport layer was about 50 nm.
[0033] Next, P2 scribing was performed using a mechanical scribe. A blade with a rectangular tip and a width of 80 μm was used as the scribing tool. The scribing tool was pressed against the ITO film using a suspension mechanism that uses a spring, and P2 mechanical scribing was performed by scanning the scribing tool parallel to the longitudinal direction of the ITO film, scraping off the three layers of the electron transport layer, perovskite layer, and hole transport layer to expose the ITO film.
[0034] Next, the second electrode (opposite electrode) was formed. The degree of vacuum was 1×10 -3 Using Pa, Ti was vacuum-deposited. The thickness of the Ti layer was 10 nm. Subsequently, at the same vacuum level, Al was vacuum-deposited to form a film. The thickness of the Al layer was about 100 nm.
[0035] Comparative Example 1 A photoelectric conversion element was produced in the same manner as in Example 1, except that in the formation of the second electrode (counter electrode) in Example 1, a Ti film was not formed, and an Al film was formed to a thickness of 100 nm by vacuum deposition.
[0036] [Evaluation of initial conversion efficiency of photoelectric conversion element and evaluation after 100 hours] The IV characteristics were measured for each of the photoelectric conversion elements of Example 1 and Comparative Example 1. The IV characteristics were measured using a solar simulator at 100 mW / cm 2 and a reference spectrum of air mass (AM) 1.5G. The measurements were performed on the initial conversion efficiency immediately after the element was fabricated and on the conversion efficiency 100 hours after fabrication. The measurement results are shown in Fig. 3, Fig. 4, and Table 1. Fig. 3 is an IV curve of Example 1, and Fig. 4 is an IV curve of Comparative Example 1, where the dotted line indicates the initial conversion efficiency immediately after the element was fabricated and the solid line indicates the conversion efficiency 100 hours after fabrication.
[0037] [Table 1]
[0038] [Observation of the counter electrode of a photoelectric conversion element] The above-mentioned photoelectric conversion element was observed by an optical microscope. The state of the second electrode (counter electrode) 100 hours after production was observed at a magnification of 10 times, and an enlarged photograph was taken. The results are shown in Fig. 5, Fig. 6, and Table 2. Fig. 5 shows the state of the Al electrode of Example 1 100 hours after production, and Fig. 6 shows the state of the Al electrode of Comparative Example 1 100 hours after production.
[0039] [Table 2]
[0040] [XPS measurement of perovskite compound layer] The photoelectric conversion element described above was subjected to XPS analysis after 100 hours of preparation. The composition analysis in the depth direction was performed while scraping in the film thickness direction from the second electrode (counter electrode) side by sputtering. The analysis results are shown in Figs. 7 to 11. Fig. 7 shows the state of the Al component at the locations corresponding to the third region, second region, and first region of the photoelectric conversion element of Example 1, and corresponds to the signal of aluminum oxide near 76 eV and metallic aluminum near 73 eV. Fig. 8 shows the Ti component near the first region, and corresponds to the signal of metallic titanium near 455 eV and 461 eV, and the signal of titanium oxide at 457 eV and 462 eV on the lower energy side. Fig. 9 is a graph showing the element abundance ratio when the horizontal axis is the depth direction, and the upper graph plots the abundance ratio of each of Al, Ti, and O on the vertical axis, and the lower graph plots the ratio of O to Al. Fig. 10 shows the state of the Al component at the locations corresponding to the third region, the second region, and the first region of the photoelectric conversion element of Comparative Example 1, and corresponds to an aluminum oxide signal at about 76 eV and a metallic aluminum signal at about 73 eV. Fig. 11 is a graph showing the element abundance ratio when the horizontal axis is the depth direction, in which the upper graph plots the abundance ratios of Al and O on the vertical axis, and the lower graph plots the ratio of O to Al.
[0041] As shown in Table 1, when the Ti electrode was laminated, the series resistance was low, the fill factor was high, and the short-circuit current density was improved, resulting in a high conversion efficiency. This is thought to be because the formation of the Ti electrode suppressed the formation of a highly resistive aluminum oxide film generated by the oxidation of the Al electrode. 100 hours after preparation, when there was no Ti electrode, the series resistance increased and the efficiency dropped significantly. The electrode's surface appearance changed as shown in Figure 6. According to the results of XPS analysis, as shown in Figures 9 and 11, the ratio of oxygen was higher than aluminum in the depth direction, and aluminum oxide signals were observed. This shows that a thick alumina film was formed in the film thickness direction, the surface changed, and the resistance increased. On the other hand, when the Ti electrode was present, there was no decrease in conversion efficiency as shown in Table 1, and no change was observed in the electrode appearance as shown in Figure 5.
[0042] From the results of the XPS analysis, as shown in Figures 7 and 9, the third region corresponding to the surface layer of the Al electrode had a higher oxygen content than aluminum and aluminum oxide was observed, while the second inner region had a higher aluminum content than oxygen, and the first region in contact with the Ti electrode had a higher oxygen content than aluminum and aluminum oxide signals were observed. Figure 9 shows that the Ti electrode is a mixed layer of titanium metal and titanium oxide. From the above, the presence of titanium oxide with n-type semiconductor properties increased rectification, increased parallel resistance, and increased fill factor, thereby increasing conversion efficiency. In addition, durability was improved due to the aluminum oxide in the first region and the titanium oxide in the Ti electrode, and conductivity was maintained due to the high aluminum content in the second region.
[0043] Example 2 A photoelectric conversion element was fabricated in the same manner as in Example 1, except that in the formation of the second electrode (counter electrode) in Example 1, Ti was vacuum-deposited to a thickness of 10 nm, followed by vacuum-depositing Al to a thickness of 100 nm, and then vacuum-depositing Ag to a thickness of 10 nm. It was confirmed that such a photoelectric conversion element also had good characteristics similar to those of Example 1.
[0044] Example 3 A photoelectric conversion element was fabricated in the same manner as in Example 1, except that in the formation of the second electrode (counter electrode) in Example 1, Ti was vacuum-deposited to a thickness of 10 nm, then Al was vacuum-deposited to a thickness of 100 nm, and then Ti was vacuum-deposited to a thickness of 10 nm. It was confirmed that such a photoelectric conversion element also had good characteristics like those in Example 1.
[0045] Although several embodiments of the present invention have been described, these embodiments are presented as examples and are not intended to limit the scope of the invention. These novel embodiments can be implemented in various other forms, and various omissions, substitutions, and modifications can be made without departing from the spirit of the invention. These embodiments and their modifications are included in the scope and spirit of the invention, and are included in the scope of the invention and its equivalents described in the claims. [Explanation of symbols]
[0046] 100...photoelectric conversion element, 110...substrate, 120...first electrode, 130...photoelectric conversion film, 140...electron transport layer, 150...second electrode, 160...first layer, 170...second layer, 171...first region, 172...second region, 173...third region, 180...third layer.
Claims
1. A substrate; A first electrode disposed on the substrate; disposed on the first electrode, Composition formula: ABX 3 (In the formula, A is a monovalent cation of an amine compound, B is a divalent cation of a metal element, and X is a monovalent anion of a halogen element.) A photoelectric conversion film including a perovskite crystal having a composition represented by the formula: an electron transport layer disposed on the photoelectric conversion film; A photoelectric conversion element comprising: a second electrode disposed on the electron transport layer, the second electrode comprises a first layer disposed on the electron transport layer and including at least one first metal selected from the group consisting of titanium, tin, zinc, cerium, indium, and niobium, and an oxide of the first metal, and a second layer disposed on the first layer and including a second metal and an oxide of the second metal; A photoelectric conversion element, wherein the second layer comprises a first region on the first layer side, a second region on the first region and having a lower oxygen concentration than the first region, and a third region on the second region and having a higher oxygen concentration than the second region.
2. The photoelectric conversion element according to claim 1 , wherein the second metal has a higher electrical conductivity than the first metal.
3. The photoelectric conversion element according to claim 2 , wherein the second metal is at least one selected from the group consisting of aluminum, molybdenum, nickel, copper, and silver.
4. The photoelectric conversion element according to claim 1 , wherein the first region and the third region have a bond between the second metal and oxygen.
5. The photoelectric conversion element according to claim 1 , wherein the second electrode further comprises a third layer disposed on the second layer and including a third metal.
6. The photoelectric conversion element according to claim 5 , wherein the third metal includes a metal that is less susceptible to oxidation than the second metal.
7. The photoelectric conversion element according to claim 6 , wherein the third metal is at least one selected from the group consisting of copper, silver, and gold.
8. The photoelectric conversion element according to claim 5 , wherein the third metal includes a metal that is more likely to form a passive state than the second metal.
9. The photoelectric conversion element according to claim 8 , wherein the third metal is at least one selected from the group consisting of titanium, aluminum, and molybdenum.
Citation Information
Patent Citations
solar cells
JP6989391B2